APLIKASI FORMULA BOKASHI KOTORAN SAPI DAN TKKS DARI SISKA BENGLULU PADA TANAMAN KELAPA SAWIT ( Elaeis guinnensis Jack) BELUM MENGHASILKAN (TBM) - Nurseha Nurseha; Sunarti Sunarti; Sri Mulatsih (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2015)
The aim of this research was to now affects of bokashi formulation made of cow manure and empty oil palm fruit bunches from SISKA Bengkulu on immature oil palm plants which had been done on January to September 2015 in Bumi Ayu village, Slebar sub-distric, Bengkulu Province.This research used Randomized Complate Block Design (RCBD) to evaluate 6 treatment were F0 = control; F1 = cow manure; F2 = 1/3 of cow manure + 2/3 of empty fruit bunch; F3 = = 1/2 of cow manure + 1/2 of empty fruit bunch; F4 == 2/3 of cow manure + 1/3 of empty fruit bunch; and F5 = empty fruit bunch.The results showed that the treatment of bokashi of cow manure and empty oil palm fruit bunches from SISKA Bengkulu had no significant affects on soil pH and changeable Al but had sicnificant effects on N, P, K, and Mg nutrients of immature oil palm plants. Control treatment (F0) = synthetic fertilizer applied at normal rate, showed the highest increasing of N,P,K, and Mg nutrient, It was sicnificantly different from all other treatments for further research (F1, F2, F3, F4, and F5), it is recommended to see the effects of fertilizing residue on the next 6 months which will be done on March 2016 to get formulation can substitute synthetic fertilizer on immature oil palm plants.Keywords: Bokashi, Tandan Kosong Sawit, kotoran sapi Siska Bengkulu